Calculation of the Phase Noise at Comb-Line Frequencies in a Frequency Comb - Anjum, Ishraq Md; Mahabadi, Seyed Ehsan Jamali; Simsek, Ergun; Menyuk, Curtis (Optica, 2021)
We calculate the phase noise in a modified uni-traveling carrier photodetector for frequency comb applications. In contrast to a continuous wave, a frequency comb is characterized by a distinct phase noise for each comb line.
Laser Science 2021 Washington, DC United States
Keywords: Ionization; Phase noise; UMBC Optical Fiber Communications Laboratory; UMBC Computational Photonics Laboratory; Frequency combs; Computer simulation; Phase; Photodetectors